Regional Variation in Residential Aged Care Provision in Australia: Targets and Trajectories - Mark Cooper-Stanbury (Journal of Long-Term Care)
Background and objectives: Population-based planning targets have been a feature of the Australian aged care policy landscape for decades. Changes in the way places are allocated are being introduced that could put at risk equitable access to residential aged places. This study sets out the regional distribution of places and shows how this might worsen under new policy arrangements.